Women Empowerment and Peacebuilding in Post-Conflict Contexts: The Role of UN Women in Jos North Local Government Area, Plateau State, 2014–2020 - Nuhu Judith Dung; Akombo I. Elijah; Surajo Ladan; Muhammed Haruna Suleimuri; Atando D. Agbu (Darul Yasin Al Sys, 2026)
Women’s participation in conflict prevention, mediation, and post-conflict recovery remains central to sustainable peacebuilding, particularly in communities affected by prolonged social and religious tensions. This study examined the role of the United Nations Entity for Gender Equality and the Empowerment of Women (UN Women) in promoting women’s empowerment and peacebuilding in Jos North Local Government Area, Plateau State, Nigeria, between 2014 and 2020. Specifically, it analysed the nature of UN Women’s empowerment programmes, evaluated their influence on women’s empowerment and participation in peacebuilding, and identified the challenges affecting the effectiveness of these interventions. Grounded in empowerment theory, the study adopted a qualitative case study design to explore collaboration between grassroots women and institutional actors in conflict prevention, mediation, and post-conflict recovery. Data were collected through semi-structured interviews, focus group discussions, and document analysis, including UN Women reports and relevant policy frameworks. The findings indicate that women in Jos North had served as first responders, informal mediators, and interfaith peacebuilders before the introduction of formal interventions. UN Women subsequently strengthened these roles through the Women Peace Mentors programme, capacity-building activities, community dialogue platforms, advocacy, and political inclusion initiatives. Although these interventions enhanced women’s visibility and participation in peacebuilding, structural, institutional, and sociocultural barriers continued to constrain sustainable empowerment. The study concludes that strengthening community-based empowerment programmes, expanding the Women Peace Mentors initiative, improving collaboration between UN Women and local stakeholders, and addressing sociocultural barriers are essential for sustaining women’s participation in peacebuilding. By providing localised empirical evidence from Northern Nigeria, the study contributes to gender and peacebuilding scholarship and offers practical insights for improving the design and implementation of women-centred peacebuilding interventions.